INVESTIGATING TEACHERS’ BELIEFS AND PEDAGOGICAL PRACTICES IN THE INTEGRATION OF ISLAMIC VALUES, ENGLISH LANGUAGE TEACHING, AND STEM EDUCATION - Awang Ali, Fariha Diyana; Radzi, Nadiah Hashim; Azizan, Ahmad Salahuddin M; Ne'matullah, Khairul Firdaus; Ab Hamid, Hafiza; Khairundin, Siti Amalina Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The integration of Islamic values, English language teaching (ELT), and STEM education reflects Malaysia’s aspiration for holistic and values-driven education. Despite increasing policy emphasis on integrated curricula, limited empirical research has examined how teachers conceptualise and enact this three-domain integration in practice. This qualitative study explores teachers’ beliefs and pedagogical practices in integrating Islamic values, English, and STEM education, focusing on their conceptual understanding, instructional challenges, and pedagogical strategies. Semi-structured interviews were conducted with purposively selected teachers teaching English and STEM-related subjects in values-oriented school contexts. Data were analysed using thematic analysis. The findings reveal three key themes: fragmented conceptualisation of integration, pedagogical tensions shaped by curriculum and assessment demands, and adaptive strategies for embedding Islamic values within language and STEM instruction. While teachers expressed strong commitment to values-based education, many struggled to operationalise integration in systematic and pedagogically coherent ways. The study contributes to the literature on integrated education by foregrounding teachers’ voices and highlighting professional development needs related to conceptual clarity, interdisciplinary pedagogy, and practical classroom enactment. Implications are discussed for teacher education and professional learning initiatives aimed at supporting meaningful integration across domains.